The Impact of Academic Supervision, School Culture, and Teacher Motivation on Learning Quality at Elementary School in Sedan District, Rembang Regency - Yulianto Hery Purnomo; Ngurah Ayu Nyoman; Muhammad Prayito (FKIP - Universitas Riau, 2026)
This study examines the impact of Academic Supervision by School Principals, School Culture, and Teacher Motivation on Learning Quality at elementary schools in Sedan District, Rembang Regency. Using a quantitative approach with multiple regression analysis, this research explores how these variables contribute to enhancing learning outcomes. Data was collected from 132 teachers across 26 elementary schools in the region through structured questionnaires and analyzed using statistical tools. The results indicate that all three independent variables have a significant positive impact on learning quality. Specifically, academic supervision by the school principal was found to have the strongest effect on the improvement of learning quality, followed by school culture and teacher work motivation. The study highlights the importance of effective academic supervision, a supportive school culture, and motivated teachers in achieving optimal educational outcomes. This research suggests that school leaders should focus on enhancing these factors to improve the quality of teaching and learning in schools. The findings contribute to understanding the factors that influence learning quality and provide insights for educational policy and practice in the context of Indonesian elementary schools.